A precursor solution and a preparation method, an environment-friendly waterproof nanometer film based on PECVD technology and a preparation method
Patent Information
- Application Number
- CN202611178386.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]但传统派瑞林材料及制备工艺存在固有环保缺陷与工艺短板,不符合当前工业RoHS、REACH环保标准及低成本、高效率的量产需求
1、本申请采用低温PECVD等离子体化学气相沉积方法进行表面改性,可批量快速对精密基材进行干法改性处理,全程无废水、废渣、废气产生,环保友好度高、无三废污染,等离子体全域轰击改性,基材异形结构、微观缝隙改性均匀性极佳。
Smart Images

Figure CN122978334A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of waterproof protection for precision devices, and mainly relates to a precursor solution and its preparation method, and an environmentally friendly waterproof nanofilm based on PECVD technology and its preparation method. Background Technology
[0002] In fields such as electronic components, precision hardware, medical devices, and smart homes, products are constantly exposed to problems such as moisture erosion, salt spray corrosion, dust pollution, and acid and alkali aging, which can easily lead to short circuits, component failures, metal corrosion, and performance degradation. Therefore, setting a waterproof protective film layer on the substrate surface is a core process to ensure product reliability.
[0003] Currently, the mainstream high-end protective film in the industry is the parylene film, which is prepared by chemical vapor deposition (CVD) process. It has the characteristics of no pinholes, strong adhesion, excellent conformability and good insulation. It can achieve all-round protection for complex structure substrates and is the core of waterproof protection for precision devices.
[0004] However, traditional Parexin materials and preparation processes have inherent environmental defects and technological shortcomings, failing to meet current industrial RoHS and REACH environmental standards and the demands for low-cost, high-efficiency mass production. Other traditional spraying and dipping waterproof coatings suffer from uneven film thickness, poor gap coverage, easy peeling, and short protective lifespan, making them unable to replace Parexin's high-end protective performance.
[0005] Therefore, developing a novel nano-waterproof membrane with structurally equivalent perylene, being green and halogen-free, low-temperature efficient, superior in performance, and capable of large-scale mass production, as well as its preparation process, is a technical challenge that urgently needs to be solved in this field. Summary of the Invention
[0006] In view of the shortcomings of the prior art, the purpose of this application is to provide a precursor solution and its preparation method, and an environmentally friendly waterproof nanofilm based on PECVD technology and its preparation method.
[0007] The technical solution of this application is as follows: A precursor solution comprising the following raw materials: hydrocarbon monomer, initiator, and solvent; The hydrocarbon monomers include one or a mixture of two of the following: closed-ring polymerizable monomers and open-ring polymerizable monomers.
[0008] Furthermore, the closed-ring polymerization monomer includes a diene cycloalkane structure monomer; The ring-opening polymerization monomers include macrocyclic regular alicyclic monomers.
[0009] Furthermore, the mass ratio of the hydrocarbon monomer, the initiator, and the solvent is (8-12):(0.5-1.5):(85-95).
[0010] This application also provides a method for preparing a precursor solution, comprising the following steps: mixing hydrocarbon monomers, initiators, and solvents to obtain a precursor solution.
[0011] This application also provides a method for preparing an environmentally friendly waterproof nanofilm based on PECVD technology, comprising the following steps: placing a substrate in a reaction chamber, introducing a vaporized precursor solution and process gas into the reaction chamber, activating plasma discharge, and performing a chemical vapor deposition reaction to form an environmentally friendly waterproof nanofilm based on PECVD technology.
[0012] Furthermore, the plasma power is 200~500W; The temperature during the deposition reaction is 40-80℃.
[0013] Furthermore, the process gas includes one or a mixture of two of high-purity argon, high-purity helium, and high-purity nitrogen. The process gas flow rate is 50~120 sccm.
[0014] Furthermore, the gas flow rate of the vaporized precursor solution is 20~100 sccm.
[0015] Furthermore, after placing the substrate in the reaction chamber, a vacuum is drawn to 0.01~10 mbar; The substrate is then subjected to plasma cleaning and pre-activation, and the vaporized precursor solution and the process gas are then introduced into the reaction chamber.
[0016] This application also provides an environmentally friendly waterproof nanofilm based on PECVD technology.
[0017] Compared with the prior art, this application has the following beneficial effects: 1. This application uses a low-temperature PECVD plasma chemical vapor deposition method for surface modification, which can rapidly perform dry modification treatment on precision substrates in batches. The entire process generates no wastewater, waste residue, or waste gas, making it highly environmentally friendly and free from pollution. The plasma bombardment modification achieves excellent uniformity in modifying irregular structures and micro-gaps in the substrate.
[0018] 2. This application innovatively adopts a dual-system hydrocarbon cycloalkane polymerization architecture, constructing a closed-loop high-density alicyclic crosslinking network and a plasma open-loop slightly regular crosslinking network, which solves the technical defects of existing single carbon-based and silicon-based protective films, such as loose crosslinking, poor wear resistance and durability, easy cracking of film layers, insufficient dimensional stability, and many stress defects. The dual-structure switchable design makes the adjustable range of film performance far superior to the traditional single-structure phenelzine and single PECVD coating systems, and has a wider range of applicable scenarios.
[0019] 3. This application utilizes a completely fluorine-free and halogen-free green preparation process, completely circumventing PFAS and halogen-related environmental restrictions. A small number of active sites can be retained within the membrane layer, supporting subsequent secondary functionalization modifications, which can further expand composite protective properties such as hydrophobicity, antibacterial properties, wear resistance, and anti-aging properties. Simultaneously, a low-temperature, low-vacuum molding process is employed, avoiding the shortcomings of traditional high-temperature, high-vacuum mass production of parabens, such as high cost and poor substrate compatibility. The membrane layer possesses high density protection, low stress flatness, and high insulation conformability, resulting in significantly superior overall protective stability and service life compared to existing protective membrane layers. Attached Figure Description
[0020] Figure 1 This is the initial test diagram for the static water contact angle test of the sample to be tested in Embodiment 1 of this application.
[0021] Figure 2 This is a test diagram of the static water contact angle test performed again on the sample to be tested in Example 1 of this application after standing at room temperature for 24 hours.
[0022] Figure 3 This is a graph showing the film thickness test results of the sample to be tested in Example 1 of this application. Detailed Implementation
[0023] The existing CVD method for preparing parylene protective films uses parylene dimer as a precursor raw material. It generates parylene active monomers through high-temperature pyrolysis under low-pressure vacuum. The active monomers are uniformly adsorbed, polymerized and cross-linked on the substrate surface to form a linear parylene polymer film. The film has the characteristics of being dense and free of pinholes, having good micro-gap coverage, being insulating and waterproof, and being resistant to aging. It is currently the best existing technology for waterproof protection of precision devices and is also the core existing technology that this application aims to replace.
[0024] The aforementioned prior art has the following disadvantages: 1. Poor environmental performance and compliance risks. The synthesis and pyrolysis process of traditional Parylene materials (especially Parylene C and Parylene D types) produces chlorine-containing harmful intermediates. The raw materials and by-products contain toxic and harmful components, which cannot meet the halogen-free, low-toxicity, and green environmental protection requirements of high-end medical devices, consumer electronics, and new energy fields. It does not comply with the latest RoHS and REACH environmental certification standards, and the export of products and their application in high-end scenarios are restricted.
[0025] 2. Stringent process conditions and extremely high mass production costs. Traditional Parexin uses CVD low-pressure high-temperature deposition process, which requires harsh conditions such as high vacuum, high temperature pyrolysis, and long-term heat preservation deposition. The equipment investment is expensive, energy consumption is high, the production cycle of a single batch is long, and the film formation rate is extremely low, which greatly increases the product protection cost and makes it difficult to adapt to the needs of large-scale industrial mass production.
[0026] 3. Shortcomings in material stability. Traditional Parylene membranes have poor resistance to ultraviolet aging. Under long-term outdoor sunlight, they are prone to molecular chain breakage, membrane powdering, cracking and peeling, resulting in rapid decline in waterproof and protective performance. At the same time, the surface hydrophobicity of the membrane is limited, and its antifouling and anti-salt spray performance is insufficient, making it unsuitable for harsh outdoor, automotive and industrial conditions.
[0027] 4. Poor process adaptability. Traditional high-temperature pyrolysis processes are not suitable for heat-sensitive substrates (flexible circuit boards, plastic precision devices, micro sensors). High-temperature environments can easily cause substrate deformation and performance damage. Furthermore, the process cannot precisely control the microstructure and thickness of the film layer, making it difficult to achieve ultra-thin nanoscale uniform film formation, which limits the protective applications of micro precision devices.
[0028] To address the shortcomings of existing traditional paraffin protective technologies, such as environmental defects, stringent processes, high costs, poor weather resistance, and weak substrate compatibility, this application develops a dual-scheme paraffin protective coating process based on two novel halogen-free hydrocarbon polymerization systems, aiming to solve the following core technical problems: 1. To solve the mass production challenges of traditional CVD processes, which involve high temperature, high vacuum, low efficiency, and high cost, a low-temperature plasma enhanced CVD (PECVD) composite polymerization process is adopted, which significantly reduces the requirements for reaction conditions, shortens the production cycle, reduces energy consumption and equipment costs, and is suitable for large-scale industrial mass production.
[0029] 2. To address the issues of poor UV aging resistance, weak hydrophobicity, and insufficient protection under harsh working conditions in traditional Perylene membranes, the micro-crosslinking structure of the membrane is optimized to improve its hydrophobicity, aging resistance, corrosion resistance, and salt spray resistance, thereby expanding the product's application scenarios.
[0030] 3. It solves the problems of poor compatibility with heat-sensitive precision substrates and low film thickness control precision of traditional processes, and realizes low-temperature plasma deposition to protect the performance of precision substrates. At the same time, it accurately prepares ultra-thin, uniform, and pinhole-free nanoscale waterproof film layers, taking into account both protection and device precision.
[0031] This application provides a precursor solution and its preparation method, as well as an environmentally friendly waterproof nanofilm based on PECVD technology and its preparation method. To make the objectives, technical solutions, and effects of this application clearer and more explicit, the following provides a more detailed description. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.
[0032] This application abandons the traditional benzene ring-containing phenelzine raw material and adopts an environmentally friendly organic precursor. Through plasma-enhanced chemical vapor deposition (PECVD) low-temperature process, it forms a dense nano-waterproof membrane layer on the substrate surface with a molecular structure similar to phenelzine, superior protective performance, and complete environmental protection. It can replace the traditional non-environmentally friendly phenelzine membrane layer.
[0033] This application provides a precursor solution comprising the following raw materials: hydrocarbon monomer, initiator, and solvent.
[0034] Hydrocarbon monomers include two optional types: The first type is closed-ring polymerizable monomers, such as 1,4-dimethylenecyclohexane, 1,3-dimethylenecyclohexane, 1,2-di(vinyl)cyclohexane, 1,2-dimethylenecyclobutane, etc., which have a diene cycloalkane structure; they can form a high-density cross-linked network structure through free radical internal cyclization. The second type is ring-opening polymerizable monomers, such as macrocyclic regular alicyclic monomers, such as Bicyclo[10.2.2]hexadecane(8CI,9CI), Bicyclo[8.2.1]tridecane, etc.; saturated cyclic structures require high-energy plasma bond breaking and ring opening, which can form low-stress regular film layers.
[0035] The mass ratio of hydrocarbon monomer, initiator, and solvent is (8-12):(0.5-1.5):(85-95).
[0036] The free radical initiator can be selected from AIBN azobisisobutyronitrile, benzoyl peroxide, potassium persulfate, α-hydroxy ketones (such as Irgacure 184) or acylphosphines (such as TPO); preferably AIBN azobisisobutyronitrile, whose thermal decomposition temperature is adapted to the low-temperature PECVD process. For closed-ring systems, it can dominate the double bond internal cyclization crosslinking reaction, and for open-ring systems, it can assist in the stable chain growth and mild crosslinking of plasma ring-opening fragments.
[0037] Inert solvents such as n-hexane, benzene, toluene, xylene, cyclohexane, carbon tetrachloride, dichloroethane, petroleum ether, liquid paraffin, and diethyl ether are preferred. n-Hexane is chemically stable, non-reactive, and has excellent compatibility with non-polar hydrocarbon monomers. It is only used for the uniform dissolution and dispersion of monomer and initiator components.
[0038] This application provides a method for preparing a precursor solution, comprising the following steps: weighing hydrocarbon monomers, initiators and solvents according to proportions, mixing the three together, stirring with an electric mixer for 10 minutes at a stirring speed of 500-1000 r / min until the mixture is homogeneous and the liquid is clear and transparent, thereby obtaining a homogeneous and stable precursor solution.
[0039] This application also provides a method for preparing an environmentally friendly waterproof nanofilm based on PECVD technology, comprising the following steps: Step 1: Substrate loading and vacuuming: Fix the substrate to the stage and perform vacuuming according to the set values.
[0040] Deposition vacuum: The vacuum in the deposition chamber is stably controlled at 0.01~10 mbar.
[0041] Step 2: Plasma cleaning and pre-activation: High-purity argon, nitrogen, or helium gas is introduced into the reaction chamber at a flow rate of 50-120 sccm. Plasma discharge is then initiated (plasma discharge power of 200-500W) and the process lasts for 2-5 minutes. This removes contaminants from the substrate surface and introduces active groups, thereby enhancing interfacial adhesion.
[0042] Step 3: Introduce the vaporized precursor solution into the reaction chamber, and simultaneously introduce process gas; activate plasma discharge. The process gas, after ionization, generates high-energy particles that bombard the vaporized precursor solution to activate it. The activated coating species undergo a chemical vapor deposition reaction with the substrate surface to form a coating layer (i.e., an environmentally friendly waterproof nanofilm based on PECVD technology), thus obtaining a coated sample.
[0043] Plasma discharge power: 200~500W, capable of stably bombarding and ionizing process gases and precursor solutions.
[0044] Process gas: One or a mixture of two of the following gases, namely high-purity argon, high-purity helium, and high-purity nitrogen, are selected as the plasma excitation and activation carrier gas.
[0045] Process gas flow rate: Controlled at 50~120 sccm to ensure uniform gas atmosphere in the chamber.
[0046] Gas flow rate of the vaporized precursor solution: 20~100 sccm, uniformly vaporized and transported to the deposition chamber.
[0047] Deposition temperature: 40~80℃.
[0048] Deposition time: preferably 5~30min; the modification time can be precisely controlled according to the morphology, specific surface area and hydrophobic protection performance requirements of the substrate to achieve controllable protective coating modification.
[0049] Step 4: After the reaction is complete, turn off the plasma discharge, depressurize the reaction chamber and restore it to normal pressure, open the equipment door and take out the coated sample.
[0050] The technical solution of this application has the following advantages: This application employs a low-temperature PECVD plasma chemical vapor deposition method for surface modification, which can rapidly perform dry modification treatment on precision substrates in batches. The entire process generates no wastewater, waste residue, or waste gas, making it highly environmentally friendly and free from pollution. The plasma bombardment modification achieves excellent uniformity in modifying irregular structures and micro-gaps in the substrate.
[0051] This application innovatively adopts a dual-system hydrocarbon cycloalkane polymerization architecture, constructing a closed-loop high-density alicyclic crosslinking network and a plasma open-loop slightly regular crosslinking network, respectively. This solves the technical defects of existing single carbon-based and silicon-based protective films, such as loose crosslinking, poor wear resistance and durability, easy cracking of the film layer, insufficient dimensional stability, and many stress defects. The dual-structure switchable design makes the adjustable range of film performance far superior to the traditional single-structure phenelzine and single PECVD coating systems, and has a wider range of applicable scenarios.
[0052] This application utilizes a completely fluorine-free and halogen-free green manufacturing process, completely circumventing PFAS and halogen-related environmental restrictions. A small number of active sites can be retained within the membrane layer, supporting subsequent secondary functionalization modifications and further expanding its composite protective properties such as hydrophobicity, antibacterial properties, wear resistance, and anti-aging properties. Simultaneously, a low-temperature, low-vacuum molding process is employed, overcoming the shortcomings of traditional high-temperature, high-vacuum mass production of paraffin films, such as high cost and poor substrate compatibility. The membrane layer possesses high density protection, low stress flatness, and high insulation conformability, resulting in significantly superior overall protective stability and service life compared to existing protective membrane layers.
[0053] This application also provides an environmentally friendly waterproof nanofilm based on PECVD technology, which can be widely used in the fields of precision electronics, medical devices, automotive components, and smart home waterproofing.
[0054] The present application will be further described below through specific embodiments.
[0055] Example 1 This embodiment provides a 1,4-dimethylenecyclohexane closed-ring crosslinked precursor solution. The raw materials include 1,4-dimethylenecyclohexane, AIBN azobisisobutyronitrile, and n-hexane, with a mass ratio of 10:1:89.
[0056] The preparation method of the 1,4-dimethylenecyclohexane closed-ring crosslinked precursor solution is as follows: Weigh 1,4-dimethylenecyclohexane, AIBN (azobisisobutyronitrile), and n-hexane according to the specified proportions. Mix the three components and stir with an electric mixer for 10 minutes at a speed of 800 r / min until the mixture is homogeneous and the liquid is clear and transparent, thus obtaining a 1,4-dimethylenecyclohexane closed-ring crosslinked precursor solution.
[0057] On the other hand, this embodiment also provides a method for preparing a closed-loop crosslinked phenelzine-like nano-waterproof membrane based on PECVD technology.
[0058] The PECVD plasma chemical vapor deposition method was used to modify the surface of the substrate for waterproof protection under vacuum conditions.
[0059] The specific steps are as follows: Step 1: Substrate loading and vacuuming.
[0060] Fix the substrate onto the stage of the PECVD equipment, close the equipment door, and evacuate the reaction chamber according to the set parameters (vacuum degree: 5mbar) to stabilize the chamber vacuum degree to the preset range.
[0061] Step 2: Plasma cleaning and activation.
[0062] High-purity argon gas is introduced at a flow rate of 80 sccm, and plasma discharge (power 300W) is initiated. Plasma activation treatment is performed for 3 minutes to remove microscopic contaminants, oil, and dust from the substrate surface. Simultaneously, active functional groups are introduced onto the substrate surface, effectively enhancing the interfacial adhesion between the film and the substrate. Step 3: The precursor solution is vaporized and introduced to react with the plasma deposition.
[0063] A vaporized 1,4-dimethylenecyclohexane closed-ring crosslinked precursor solution is uniformly introduced into the reaction chamber, while process gas is continuously introduced simultaneously.
[0064] When plasma discharge is initiated, the specific parameters during the plasma deposition reaction are as follows: plasma discharge power: 300W; process gas: argon; process gas flow rate: 80sccm; gas flow rate of the vaporized precursor solution: 65sccm; deposition temperature: 60℃; deposition time: 20min.
[0065] The process gas generates high-energy particles after plasma ionization, which bombard and activate the vaporized precursor solution, triggering intracyclization of monomer double bond free radicals and intermolecular cross-linking reactions. The activated active species of the coating undergo chemical vapor deposition reaction with the substrate surface, resulting in the in-situ growth of a high-density closed-loop network protective coating layer on the substrate surface.
[0066] Step 4: Break the vacuum in the cavity and remove the sample.
[0067] After the reaction is complete, the plasma power supply, precursor solution delivery and process gas supply are turned off. The reaction chamber is slowly depressurized and restored to atmospheric pressure. The equipment door is opened, the modified substrate is taken out, and the preparation of the closed-loop crosslinked phenelzine-like nano-waterproof membrane based on PECVD technology is completed and its performance is tested.
[0068] In the synergistic environment of plasma and AIBN radicals, the terminal vinyl double bonds of the 1,4-dimethylenecyclohexane monomer undergo selective activation and cleavage, generating highly reactive carbon radical fragments. Simultaneously, multiple polymerization reactions occur within the system: monomer double-bond radicals homopolymerize to form rigid hydrocarbon chains; radical-induced intramolecular cyclization forms closed-ring alicyclic structures; and intermolecular cross-linking occurs between reactive carbon radicals, gradually constructing a high-density, high-strength three-dimensional closed-ring hydrocarbon cross-linked network.
[0069] The technical principle of closed-loop crosslinked phenelzine-like nano-waterproof membrane based on PECVD technology is as follows: Under normal temperature vacuum conditions, a set vacuum level is achieved by evacuation. High-purity argon, nitrogen, or helium is introduced to generate plasma. Subsequently, the prepared precursor solution is vaporized. The vaporized gaseous precursor and process gas enter the vacuum chamber and are bombarded and ionized by high-energy particles in the plasma atmosphere, resulting in the breaking of chemical bonds and the generation of active free radicals. Simultaneously, the substrate surface is activated by plasma bombardment, generating a large number of surface-active groups. These surface-active groups react chemically with the free radicals generated by the precursor ionization, forming crosslinks and bonds. Ultimately, a dense and stable hydrophobic protective film is uniformly deposited on the substrate surface, achieving long-term hydrophobic modification of the substrate surface. This method is a dry modification method using plasma chemical vapor deposition.
[0070] Example 2 The difference from Example 1 is that the raw materials for preparing the precursor solution include the macrocyclic alicyclic monomer Bicyclo[10.2.2]hexadecane (8CI,9CI), AIBN azobisisobutyronitrile, and n-hexane.
[0071] Comparative Example 1 The difference from Example 1 is that the precursor solution is replaced with p-xylene dimer.
[0072] The remaining preparation processes and parameters are the same as in Example 1, and will not be repeated here.
[0073] Comparative Example 2 Except for the elimination of the plasma high-energy ring-opening excitation condition and the use of simple thermally initiated polymerization to prepare the film, the preparation process and parameters of this comparative example are the same as those of Example 2.
[0074] Step three involves uniformly introducing the vaporized precursor solution into the reaction chamber at a flow rate of 65 sccm, heating to 60°C, and maintaining this temperature for 20 minutes to form a coating layer. Performance testing: Testing standards: The static water contact angle was tested according to GB / T 30447-2013 "Method for measuring contact angle of nanofilms".
[0075] The film thickness was tested according to GB / T 26332-2010 "Methods for measuring the thickness of optical thin films".
[0076] The test for resistance to ultraviolet yellowing is based on GB / T 23987.3-2025 "Laboratory light source exposure methods for paints and varnishes - Part 3: Fluorescent ultraviolet lamps".
[0077] The test results are shown in Tables 1 and 2: Table 1
[0078] The data in the table above show that Example 1 exhibits the best overall performance, with a film thickness of 258.5 nm, an initial static water contact angle of 137.6°, and a static water contact angle greater than 130° even after 24 hours of standing. Compared to Example 1, the film thickness and contact angle of Examples 2 and Comparative Examples 1, 2, and 3 are relatively poor. This is because Example 1 uses a diene cycloalkane monomer, which possesses abundant double-bond crosslinking active sites. Combined with a free radical initiation system, it can achieve efficient internal ring crosslinking, constructing a high-density three-dimensional closed-ring network crosslinking network, resulting in a higher crosslinking density, higher deposition efficiency, and more complete film growth. In addition, the closed-ring alicyclic rigid framework structure has stronger stability, resulting in sufficient film thickness, a higher static water contact angle, and better hydrophobic stability. In Example 2, only a mild cross-linking structure is formed by plasma ring opening, and the cross-linking density is relatively low. Each comparative example can only form a single linear structure or a single inorganic cross-linking network. There are few effective cross-linking active sites, low degree of polymerization reaction, and loose molecular chain segment stacking. The film uniformity and density are insufficient, so the film thickness is thin, the hydrophobic contact angle is low, and the overall protective stability is poor.
[0079] The static water contact angle of the sample surface in Example 1 was tested using a contact angle measuring instrument. The results showed that the initial static water contact angle of the sample surface was 137.578° (refer to...). Figure 1 This indicates that it possesses excellent hydrophobic properties. To further evaluate the stability of the film, the sample was left to stand at room temperature for 24 hours before being tested again. Its contact angle remained at 134.214° (refer to...). Figure 2 This demonstrates that the modified layer (a closed-loop crosslinked, perine-like nano-waterproof membrane based on PECVD technology) has good and long-lasting hydrophobic stability.
[0080] The film thickness of the sample surface in Example 1 was measured using a film thickness meter. (See attached image.) Figure 3 As shown, the film thickness on the surface of the sample can reach over 250 nm, with sufficient thickness and good deposition uniformity, directly demonstrating excellent plasma deposition film formation effect. This proves that diene-modified precursors are highly compatible with PECVD low-temperature deposition processes as coating materials, exhibiting high film formation efficiency, sufficient film growth, and the ability to stably form high-performance hydrophobic protective films with sufficient thickness, dense structure, and excellent static water contact angle.
[0081] Table 2
[0082] As shown in the table above, Example 1 performed best in the UV yellowing resistance test. In terms of appearance, neither Example 1 nor Example 2 showed yellowing, detachment, peeling, or powdering, while Comparative Example 1 showed slight yellowing, and Comparative Example 2 showed significant yellowing and detachment, peeling, and powdering. This indicates that the closed-ring alicyclic rigid framework and high-density cross-linked network used in the embodiments of this invention have strong UV aging resistance and can effectively inhibit the degradation and discoloration of the film under UV irradiation.
[0083] Regarding the contact angle, Example 1 showed a decrease of only 2.4° after aging, while Example 2 showed a decrease of 2.6°, demonstrating excellent hydrophobic stability. Comparative Example 1 showed a decrease of 5.6°, and Comparative Example 2 showed a significant decrease of 30.3°, indicating a substantial decline in hydrophobic performance. This suggests low crosslinking density and loose molecular chains, making the film structure easily damaged under UV irradiation. Considering both the appearance and the changes in contact angle, it is clear that the UV aging resistance and hydrophobic durability of the examples in this application are significantly superior to those of the comparative examples.
[0084] It should be understood that the application of this application is not limited to the examples above. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of this application.
Claims
1. A precursor solution, characterized in that, The preparation materials include: hydrocarbon monomers, initiators, and solvents; The hydrocarbon monomers include one or a mixture of two of the following: closed-ring polymerizable monomers and open-ring polymerizable monomers.
2. The precursor solution according to claim 1, characterized in that, The closed-ring polymerization monomer includes a diene cycloalkane structure monomer; The ring-opening polymerization monomers include macrocyclic regular alicyclic monomers.
3. The precursor solution according to claim 1, characterized in that, The mass ratio of the hydrocarbon monomer, the initiator, and the solvent is (8-12):(0.5-1.5):(85-95).
4. A method for preparing a precursor solution based on any one of claims 1-3, characterized in that, Includes the following steps: The hydrocarbon monomer, initiator, and solvent are mixed to obtain a precursor solution.
5. A method for preparing an environmentally friendly waterproof nanofilm based on PECVD technology, characterized in that, Includes the following steps: The substrate is placed in the reaction chamber, and the vaporized precursor solution and process gas are introduced into the reaction chamber. Plasma discharge is turned on to carry out chemical vapor deposition reaction to form an environmentally friendly waterproof nanofilm based on PECVD technology. The precursor solution is a precursor solution prepared based on any one of the precursor solutions according to claims 1-3 or based on the preparation method of the precursor solution according to claim 4.
6. The method for preparing an environmentally friendly waterproof nanofilm based on PECVD technology according to claim 5, characterized in that, In chemical vapor deposition, the plasma discharge power is 200~500W and the temperature is 40-80℃.
7. The method for preparing an environmentally friendly waterproof nanofilm based on PECVD technology according to claim 5, characterized in that, The process gas includes one or a mixture of two of high-purity argon, high-purity helium, and high-purity nitrogen. The process gas flow rate is 50~120 sccm.
8. The method for preparing an environmentally friendly waterproof nanofilm based on PECVD technology according to claim 5, characterized in that, The gas flow rate of the vaporized precursor solution is 20~100 sccm.
9. The method for preparing an environmentally friendly waterproof nanofilm based on PECVD technology according to claim 5, characterized in that, After placing the substrate in the reaction chamber, a vacuum is drawn to 0.01~10 mbar; The substrate is then subjected to plasma cleaning and pre-activation, and the vaporized precursor solution and the process gas are then introduced into the reaction chamber.
10. An environmentally friendly waterproof nanofilm based on PECVD technology prepared by the preparation method of the environmentally friendly waterproof nanofilm based on any one of claims 5-9.